2004
DOI: 10.1021/ic0303237
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer to Nickel−Thiolate Complexes. 2. Rate-Limiting Intramolecular Proton Transfer in the Reactions of [Ni(SC6H4R-4)(PhP{CH2CH2PPh2}2)]+ (R = NO2, Cl, H, Me, or MeO)

Abstract: The protonation of [Ni(SC(6)H(4)R-4)(triphos)](+) (triphos = PhP[CH(2)CH(2)PPh(2)](2); R = NO(2), Cl, H, Me, or MeO) by [lutH](+) (lut = 2,6-dimethylpyridine) to form [Ni(S(H)C(6)H(4)R-4)(triphos)](2+) is an equilibrium reaction in MeCN. Kinetic studies, using stopped-flow spectrophotometry, reveal that the reactions occur by a two-step mechanism. Initially, [lutH](+) rapidly binds to the complex (K(2)(R)) in an interaction which probably involves hydrogen-bonding of the acid to the sulfur. Subsequent intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…These two values are slightly different from the values (0.18 and 0.064(1) Å, respectively) found in the closely related structure [NiCl(PhP{CH 2 CH 2 PPh 2 } 2 )] + (D) 34 and are attributed to the relatively smaller size of the oxygen atom in ligand 1 than the carbon atom of the ligand in D. The P1–Ni–P3 angle of 161.7(1)° and the P2–Ni1–Cl1 angle of 169.9(1)° are not differing much from the analogous angles (162.4(1)° and 171.6(1)°) in the reported complex D. The Ni–Cl bond distance of 2.1685(7) Å is close to 2.169(3) Å in complex D. The central phosphorus P2–Ni distance of 2.1067(7) Å is slightly shorter than the other two P–Ni distances (2.1978(6) Å and 2.1949(6) Å) owing to the stronger trans influence of phosphorus than the chlorine atom and to the nature of atoms (two oxygens and one aryl carbon to the central P2; two aryl and one alkyl carbons to P1 and P3) attached to the phosphorus atom. Similar trend has been observed in the reported four coordinate Ni( ii ) square planar complexes such as D, [Ni(SR)(PhP{CH 2 CH 2 PPh 2 } 2 )] + (R = Et, t Bu, Cy, 35 Bn 36 and Ph 37 ) and in the five coordinate square pyramidal Ni( ii ) complex C.…”
Section: Resultssupporting
confidence: 89%
“…These two values are slightly different from the values (0.18 and 0.064(1) Å, respectively) found in the closely related structure [NiCl(PhP{CH 2 CH 2 PPh 2 } 2 )] + (D) 34 and are attributed to the relatively smaller size of the oxygen atom in ligand 1 than the carbon atom of the ligand in D. The P1–Ni–P3 angle of 161.7(1)° and the P2–Ni1–Cl1 angle of 169.9(1)° are not differing much from the analogous angles (162.4(1)° and 171.6(1)°) in the reported complex D. The Ni–Cl bond distance of 2.1685(7) Å is close to 2.169(3) Å in complex D. The central phosphorus P2–Ni distance of 2.1067(7) Å is slightly shorter than the other two P–Ni distances (2.1978(6) Å and 2.1949(6) Å) owing to the stronger trans influence of phosphorus than the chlorine atom and to the nature of atoms (two oxygens and one aryl carbon to the central P2; two aryl and one alkyl carbons to P1 and P3) attached to the phosphorus atom. Similar trend has been observed in the reported four coordinate Ni( ii ) square planar complexes such as D, [Ni(SR)(PhP{CH 2 CH 2 PPh 2 } 2 )] + (R = Et, t Bu, Cy, 35 Bn 36 and Ph 37 ) and in the five coordinate square pyramidal Ni( ii ) complex C.…”
Section: Resultssupporting
confidence: 89%
“…www.chemeurj.org complexes that involve, for example, initial protonation at the nickel center or at the thiolate ligands. [30][31][32][33][34] Transient breakage of one RuÀS bond might also occur in such coordinatively saturated complexes, even if the DFT calculations carried out in this study never found such hemi-lability of…”
Section: Electrochemical Properties: Cyclic Voltammograms Of Com-mentioning
confidence: 62%
“…An interesting feature of the nickel-thiolate moiety is its ability to support ligand protonation without subsequent protonolysis [12][13][14]. This is most often observed in (near) square planar Ni 2+ centers where the nucleophilic HOMO possesses significant S(3pπ) character, which effectively act as S-based lone-pairs.…”
Section: Introductionmentioning
confidence: 99%